Non-Verbal Representation of the Concept Sphere “Mother “In Novels of English (Zien Journal of Social Sciences and Humanities, 2022)
The article deals with the ways of representing non-verbal communication of the conceptual sphere “Mother” in English literary texts. Gestures and facial expressions as the main features non-verbal communication are portrayed in literary texts not only in isolation, but in combination with each other. The use of non-verbal features in English literary texts are transmitted to their speaking manner, culture of communication and other characteristics. The knowledge of peculiarities of using non-verbal features contributes to the effectiveness of communication.